Training and mentoring of Health Workers and Cadres of Bengkulu City Health Center in Monitoring The Growth and Development of Toddlers with The SDIDTK Application - Kurniati, Neng; Novianti, Novianti; Ramadhaniati, Fitri; Yora Saki, Vernonia (Teumulong: Journal of Community Service, 2024)
Monitoring children's growth and development is one of the basic programs implemented by Community health center (Puskesmas) to ensure a healthy life and improve children's welfare. The Bengkulu City Health Office identified limited human resources and a lack of supporting tools as inhibiting factors in achieving SDIDTK service targets. The service was carried out through training on Growth and Development Monitoring with the Android-based SDIDTK Application and field assistance. The training was held on July 24-25, 2024 with 36 participants consisting of 17 health workers, 17 cadres from 17 health centers, and 2 staff from the Family Welfare Division of the Bengkulu City Health Office at the Campus 4 Hall of Bengkulu University. The results of the pre and post-test of the training showed that 94% of participants increased their knowledge. The results of the assessment of skills in using the application showed that 100% of participants were able to do as directed. SDIDTK Kit assistance was delivered to 17 Puskesmas with the signing of the Minutes by the Head of Service implementer and staff of the Health Division of the Bengkulu City Health Office. Field assistance was carried out for 2 weeks after the training in 17 Puskesmas working areas.